Impaired NK cell activation during acute dengue virus infection: A contributing factor to disease severity - Snehal Shabrish; Niteen Karnik; Vishal Gupta; Priya Bhate; Manisha Madkaikar (Heliyon, 2020)
Dengue viral (DENV) infection has a broad clinical spectrum ranging from classical febrile illness to life-threatening disease. Literature suggests that spectrum of illness could be due to differences in innate immune-responses; however, the knowledge is still at infancy. Amongst the various cells involved in innate immune responses, NK cells play a central role, particularly in anti-viral immunity. Thus in this study we have evaluated the role of NK-cells during acute-DENV infection and its influence on severity of disease, by analyzing activation, cytotoxic receptors, cytolytic granule contents and degranulation markers on NK-cells during different stages of infection.Based on the clinical manifestations and severity of the disease, DENV patients were classified into patients with dengue without warning signs (DF), dengue with warning signs (DFWS) and severe dengue (SD) patients. During acute-DENV infection, though there was no alteration in frequency of NK-cells, significant increase in frequency of CD56bright subset in DF patients (p < 0.05) was observed, while it remained unaltered in SD patients. We also found that, CD56dim NK-cell subset of DF patients had elevated CD69 expression, granzyme B and intracellular IFN-γ levels compared to SD patients (p < 0.05). Amongst the NK-cell cytotoxicity receptor (NCR), NKp30 receptor was significantly elevated in DF patients (p < 0.05), however in SD patients it was comparable to healthy controls. This receptor is essential for dendritic cells-NK-cells crosstalk for initiating adaptive immune response. IL-15 is known to induce NKp30 expression, which was also seen to be elevated in DF patients (p < 0.05) but unaltered in SD patients. In SD patients, even post-6 days of infection i.e. during recovery phase, CD69 and NKp30 expression did not raise, suggesting impaired NK-cell response in these patients.To summarize, our study reports, that efficient NK cell response during acute phase of DENV infection is crucial for preventing severity of the disease. This study helps in understanding the dynamics of NK cell response in immunopathogenesis of DENV infection; which is crucial for development of efficacious therapeutics as well as vaccine.